Solve your doubts and expand your knowledge with IDNLearn.com's extensive Q&A database. Get prompt and accurate answers to your questions from our experts who are always ready to help.
Sagot :
To solve the equation [tex]\(\frac{1}{\csc^2 x} + \cos^2 x = 1\)[/tex], let's break it down step by step.
1. Understand the Terms:
- [tex]\(\csc x\)[/tex] is the cosecant of [tex]\(x\)[/tex], which is the reciprocal of the sine function: [tex]\(\csc x = \frac{1}{\sin x}\)[/tex].
- Therefore, [tex]\(\csc^2 x = \left( \frac{1}{\sin x} \right)^2 = \frac{1}{\sin^2 x}\)[/tex].
2. Rewrite the Equation:
Substitute [tex]\(\csc^2 x\)[/tex] in the equation:
[tex]\[ \frac{1}{\csc^2 x} = \sin^2 x \][/tex]
So, the original equation can be written as:
[tex]\[ \sin^2 x + \cos^2 x = 1 \][/tex]
3. Use the Pythagorean Identity:
Recall the fundamental Pythagorean identity in trigonometry:
[tex]\[ \sin^2 x + \cos^2 x = 1 \][/tex]
4. Compare the Equations:
Notice that our restructured equation [tex]\(\sin^2 x + \cos^2 x = 1\)[/tex] is exactly the same as the established Pythagorean identity. Hence, the equation is always true for all [tex]\(x\)[/tex].
5. Conclusion:
Therefore, simplifying the given trigonometric equation [tex]\(\frac{1}{\csc^2 x} + \cos^2 x = 1\)[/tex] results in the identity [tex]\(1 = 1\)[/tex], which simplifies to:
[tex]\[ 0 = 0 \][/tex]
This confirms that the given equation holds true for all values of [tex]\(x\)[/tex]. Hence, the simplified form of the given equation is [tex]\(0\)[/tex].
1. Understand the Terms:
- [tex]\(\csc x\)[/tex] is the cosecant of [tex]\(x\)[/tex], which is the reciprocal of the sine function: [tex]\(\csc x = \frac{1}{\sin x}\)[/tex].
- Therefore, [tex]\(\csc^2 x = \left( \frac{1}{\sin x} \right)^2 = \frac{1}{\sin^2 x}\)[/tex].
2. Rewrite the Equation:
Substitute [tex]\(\csc^2 x\)[/tex] in the equation:
[tex]\[ \frac{1}{\csc^2 x} = \sin^2 x \][/tex]
So, the original equation can be written as:
[tex]\[ \sin^2 x + \cos^2 x = 1 \][/tex]
3. Use the Pythagorean Identity:
Recall the fundamental Pythagorean identity in trigonometry:
[tex]\[ \sin^2 x + \cos^2 x = 1 \][/tex]
4. Compare the Equations:
Notice that our restructured equation [tex]\(\sin^2 x + \cos^2 x = 1\)[/tex] is exactly the same as the established Pythagorean identity. Hence, the equation is always true for all [tex]\(x\)[/tex].
5. Conclusion:
Therefore, simplifying the given trigonometric equation [tex]\(\frac{1}{\csc^2 x} + \cos^2 x = 1\)[/tex] results in the identity [tex]\(1 = 1\)[/tex], which simplifies to:
[tex]\[ 0 = 0 \][/tex]
This confirms that the given equation holds true for all values of [tex]\(x\)[/tex]. Hence, the simplified form of the given equation is [tex]\(0\)[/tex].
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! Thank you for choosing IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more solutions.